Euterpe edulis seed germination parameters and genotype selection - José Henrique Soler-Guilhen (Acta Scientiarum. Agronomy, 2020)
The palm tree juçara (Euterpe edulis Mart) is considered one of the most important and threatened native species in the Atlantic Forest. The search for juçara seeds (Euterpe edulis Martius) has increased, generating a need for technologies favorable to their production, quality and conservation. The aim of this study was to describe the seed germination patterns of 45 juçara accessions by using a nonlinear model to examine the behavior of these patterns and select superior genotypes. After clustering 45 juçara accessions into four groups, four nonlinear models, namely, the logistic, Gompertz, von Bertalanffy and Weibull models, were tested based on their fit for each group of accessions. The Gompertz model presented the best fit to describe the germination growth curve of E. edulis seeds. Groups 3 and 4 presented the highest daily germination rates and were considered the most vigorous. Analysis of deviance was performed, revealing genetic variability among the genotypes in terms of seed germination and vigor. It was possible to find a nonlinear model that best explained our data, and this model may also be a promising model for other palm tree species. It is possible to select genotypes based on the characters we analyzed, due to the elevated genetic variability.